Kejadian Pertusis di Kelurahan Jatingaleh, Kecamatan Candisari, Kota Semarang Tahun 2024 - Tristanti, Wita Istiqomah; Muh, Fauzi; Adi, Mateus Sakundarno; Martini, Martini; Suhartono, Suhartono (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: Pertussis is a respiratory disease caused by the bacteria Bordetella pertussis. In Semarang City, from 2022-2023, no cases of pertussis were found. On June 18, 2024, the Semarang City Health Office received a report of 2 pertussis suspects from the primary health center with complaints of coughing for two weeks accompanied by vomiting, and a "whoop" sound after taking a breath. The purpose of this epidemiological investigation is to comprehensively describe the incidence of pertussis in Semarang City in 2024 and prevent wider spread. Methods: The type of research in the investigation of pertussis incidents in Semarang City in 2024 is a descriptive case study. The population of this study were children aged 1 to 5 years who lived in the Karangpanas RW 1 Jatingaleh, Candisari, Semarang City. The sample of this study was children aged 1 to 5 years who were confirmed positive for pertussis. The variables studied were gender, history of coughing, vomiting, and DPT immunization. Data were collected through direct observation and interviews with parents/guardians. Data analysis is presented descriptively to determine the distribution of frequency of occurrence. Results: PCR results stated that both suspects were positive for Bordotella sp. bacteria. The highest attack rate value was respondents who did not have a history of DPT immunization. Conclusion: H and Y were confirmed as pertussis cases based on PCR examination. A history of never receiving DPT immunization was the cause of the highest attack rate in the pertussis incident in Semarang City in 2024.Keywords: Pertussis, immunization, children, Semarang.